Mass influx refugee situations: law and practice - Chuula, Luyando (Department of Public Law, 2017)
The problem of refugees is a global one that is of concern to all states. There are rising numbers of refugees that are forced to migrate from their homes in search of safety. How states respond to refugee situations is very important for the protection of refugee's rights. The international community has been able to draft some international conventions and treaties that provide for the protection of refugees. However, most are drafted in a manner that caters for individual determination and protection procedures. This is despite the fact that refugees enter countries in large groups most times. The major international laws that that cater for group situations are not exact on who must take on the responsibility in mass influx situations, how this responsibility should be shared and also the form and manner that the responsibility sharing mechanisms should take. This research is an insight into the laws and current practise of state in times of mass influx refugee situations. The current crisis in Syria is an example of mass influx situations and how states have been handling the situation and this research analyses the Syrian situation in order to understand current state practice. The research also explores the laws that are currently in place to protect refugees and if they can be applied to mass influx situations while adequately guaranteeing the protection of the human rights of the refugees. It further explores the options that are open to states in times of mass influx, state practice and the obligations that should arise in such situations.